Patients' Voices, Rights and Responsibilities: On Implementing Social Audit in Primary Health Care - Hill, Wang Ying (Journal of business ethics, 1998)
This paper reports on an interpretive research project which examines the feasibility of implementing social audit within the general medical practice setting. The study aims to communicate patients' voices to aid evaluation of the potential contribution of social audit to the public health sector and also addresses particular conceptual problems which arise when attempting to implement social audit within this environment. The fieldwork focuses on one general health practice in Lanarkshire (in southern central Scotland). Consultative focus group discussions and individual interviews were carried out with a sample of twenty two patients. Patients were most concerned with health service organisational and delivery issues. Overall, the results suggest patients are enthusiastic about the ideas and process of the social audit. Patients were able to demonstrate a capacity for grasping accountability issues and balanced reasoning. There was an acute awareness of the constraints which exist in the public services. Patients addressed the broad rights and responsibilities issues, and highlighted the possible pitfalls of relying on a representational mechanism for ensuring their voices were heard. The study concludes that an involved and negotiative dialogue process of implementing social audit could provide beneficial understanding and ideas to the organisation which may be further researched.